1994
DOI: 10.1177/074355489493002
|View full text |Cite
|
Sign up to set email alerts
|

Social Support as a Factor in African-American Adolescents' Sexual Risk Behavior

Abstract: African-American adolescents (N = 295) reporting high or low levels of social support completed measures of AIDS knowledge, health locus of control, attitudes toward condoms, self-reported sexual behavior for the preceding 12 months, perceptions of personal HIVrisk, and self-and response-efficacy ratings. Adolescents with less social support were less knowledgeable about AIDS, held more negative attitudes toward condoms, and were lower in selfefficacy than adolescents with higher levels of social support. Adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Participants who reported that their social norms favored condom use were significantly less likely to engage in unprotected anal and/ or vaginal sex with a female partner in the past 12 months. Consistent with previous research, 48,[51][52][53][54][55][56] strong community norms supporting the acceptability of condom use may assist or encourage safer sexual behavior among Black MSM. This seems particularly likely given that lower rates of UAS were observed in our sample among Black MSM reporting last sex with Black male nonmain (casual/hook-up) sex partners.…”
Section: Discussionsupporting
confidence: 76%
“…Participants who reported that their social norms favored condom use were significantly less likely to engage in unprotected anal and/ or vaginal sex with a female partner in the past 12 months. Consistent with previous research, 48,[51][52][53][54][55][56] strong community norms supporting the acceptability of condom use may assist or encourage safer sexual behavior among Black MSM. This seems particularly likely given that lower rates of UAS were observed in our sample among Black MSM reporting last sex with Black male nonmain (casual/hook-up) sex partners.…”
Section: Discussionsupporting
confidence: 76%
“…Findings of two studies supported positive effect of social support on promoting safer sexual behaviors among adolescents. One study conducted among African American adolescents in the U.S. suggested that adolescents with higher perceived general social support, as measured by the Social Provisions Scale [32], were less likely to engage in casual sex, have more sexual partners, report more frequent coercions into unwanted sex, and show higher rates of STIs [77]. Another study conducted in Ghana indicated that male adolescents with a higher level of social support were more likely to have used a condom [78].…”
Section: Resultsmentioning
confidence: 99%
“…Factor analysis yielded a six factor structure as follows: (a) relationship safety; (b) perceived risk; (c) interpersonal impact; (d) safety; (e) effect on sexual experience; and (f) promiscuity. The CASA showed internal consistency (Cronbach's alpha = .80), with an overall test-retest reliability of .84 (St. Lawrence et al 1994). The total scale score (range: 0-20) was used as the dependent measure of youth's overall attitude toward condoms.…”
Section: Methodsmentioning
confidence: 97%
“…The Condom Attitude Scale-Adolescent Version (CASA; St. Lawrence et al 1994) measures attitudes regarding condom use. It is a 23-item, true-false questionnaire.…”
Section: Methodsmentioning
confidence: 99%